Parallel numerical algorithms for optimization of electrical cables - Čiegis, Raimondas; Čiegis, Remigijus; Meilūnas, Mečislavas; Jankevičiutė, Gerda; Starikovičius, Vadimas (Mathematical Modelling and Analysis, 2008)
In this paper we propose new heuristic numerical algorithm for determination of the optimal wires diameters in electrical cables. Two multilevel parallel versions of the optimization algorithm are constructed. The first algorithm is based on master‐slave technique and the second algorithm uses the data‐parallel strategy. Multilevel structure of the algorithms gives a possibility to adapt them to parallel architecture, for example, cluster of multicore computers. Some results of numerical experiments are presented which agree well with theoretical analysis.First Published Online: 14 Oct 2010